STUDENT PERSPECTIVES ON THE EFFECTIVENESS OF E-PORTFOLIO BASED DIGITAL MODULES IN A HYBRID LEARNING ENVIRONMENT: A CASE STUDY IN BUSINESS ADMINISTRATION - I Putu Yoga Laksana; Ni Ketut Suciani; Gary P. Boyce; Putu Tika Virginiya; Ni Wayan Sadiyani (Curricula : Journal of Teaching and Learning, 2023)
This study explores students' perceptions regarding the effectiveness of e-portfolio-based digital modules in a hybrid learning environment. The study involved 77 students in the Business Administration Department of a vocational college during the 2021/2022 academic year. Data was collected through a questionnaire with five aspects of e-module implementation and semi-structured interviews. The results indicate that the e-module created has a substantial impact on students' learning, both online and offline. Experts have previously indicated that e-portfolios allow students to build their independent learning environments, and students in this study confirm that access to electronic modules through smartphones offers a new learning approach. However, further development of the module into web-based materials is recommended to help students learn more efficiently. Overall, the integration of e-portfolio-based digital modules in a hybrid learning environment provides students with positive effects on their independent learning process.